Impact of functional speed training on speed-related parameters and performance in youth basketball players - Ersoy, Buse; Bilge, Murat; Caglar, Emine; Michalsik, Lars Bojsen (Progress in Nutrition, 2020)
Study Objectives: The purpose of this study was to examine the impact of functional sprint training on the movement components affecting speed in youth basketball players. Methods: The subjects in this study consisted of three groups; a research group (RG, age=12,5 ± 0,3, n=16), a basketball group (BG, age=12,5 ± 0,3, n=16), and a control group (CG, age=12,2 ± 0,4, n=16). In addition to normal basketball training RG performed functional sprint training known as A-B-C training while. BG performed only basketball training. CG did not perform any kind of training. The subjects in the RG and BG carried out a total of 24 training sessions during in eight-week period with 3 times x 45 min´s training per week. All three groups were tested before and after the functional sprint training intervention using a group of well-known agility and sprint tests (Illinois, T-drill, 505 agility test, and a 20-m acceleration test). Results: Differences were found between BG and CG in the percentage of developmental values in 10-20 m (p <0.05) in favor of BG, between RG and both BG and CG in the T-drill and Illinois agility test percentage of developmental values (p <0.01) in favor of RG and between CG and both RG and BG in the 505 agility test percentage of developmental values (p <0.05) against CG. Conclusion: The present findings show that 8 weeks of functional sprint training performed 3 times x 45 min per week had a marked effect on some movement components influencing speed ability in youth basketball players.